FROM CONFLICT TO COOPERATION: HOW SYNTHETIC RUBBER INSTRUMENTAL IN CULMINATING JAPAN-ASEAN TIES - Md Akhir, Md Nasrudin (WILAYAH: The International Journal of East Asian Studies, 2023)
This article analyzes the overview of Japan-ASEAN relations since their interaction 50 years ago. Japan-ASEAN relations in the late 1960s and early 1970s were less encouraging due to dissatisfaction involving the issue of synthetic rubber in 1972-1974 as well as the unwelcoming response during Kakuei Tanaka’s visit to five ASEAN member countries in 1974. This article partly uses a primary source obtained from the National Archives of Malaysia which is a declassified documents prepared in December 1972 by officials from Malaysia’s main ministries on the threat of Japanese synthetic rubber. It is necessary to state that the approach taken by these bureaucrats is through a "softening up" measure instead of “hard-bargaining tactics” to find the best solution by proposing the ASEAN platform as a strategy for dealing with the Japanese government. This article provides a laconic view of the extent to which Japan’s relations with ASEAN encountered difficulties along the journey before arriving to the current phase. The relationship has reflected strong resilience and bond based on mutual interests and shared responsibility in promoting regional harmony and development.